2021
DOI: 10.3390/met11081241
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Properties of Oxide Coatings with Immobilized Zeolites Obtained by Plasma Electrolytic Oxidation of Aluminum

Abstract: In this paper, we employed plasma electrolytic oxidation (PEO) of aluminum in a water solution of sodium tungstate (Na2WO4∙2H2O) with the addition of the pure and Ce-loaded zeolites clinoptilolite and 13 X for the preparation of oxide coatings. The obtained coatings were characterized with respect to their morphologies and chemical and phase compositions using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy, atomic force microscopy, and X-ray diffraction. The prepared coatings co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Thus, the trend in the Rct of the samples was: uncoated TiAl (49.6 kΩ m 2 ) < 400 V (280.1 kΩ m 2 ) < 450 V (380.2 kΩ m 2 ) < 500 V (456.7 kΩ m 2 ). In this regard, some researchers [80][81][82][83][84][85][86][87][88][89][90][91] have suggested that the substantial corrosion resistance in PEO coatings stems from the thickness of the oxide layer. Therefore, as the voltage rose, a thicker PEO film formed, which causes the penetration rate of the corrosive solution into the substrate to decrease; hence the chemical reactions culminating in the coating formation deaccelerated kinetically and thermodynamically.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Thus, the trend in the Rct of the samples was: uncoated TiAl (49.6 kΩ m 2 ) < 400 V (280.1 kΩ m 2 ) < 450 V (380.2 kΩ m 2 ) < 500 V (456.7 kΩ m 2 ). In this regard, some researchers [80][81][82][83][84][85][86][87][88][89][90][91] have suggested that the substantial corrosion resistance in PEO coatings stems from the thickness of the oxide layer. Therefore, as the voltage rose, a thicker PEO film formed, which causes the penetration rate of the corrosive solution into the substrate to decrease; hence the chemical reactions culminating in the coating formation deaccelerated kinetically and thermodynamically.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…it entirely depends on content of Ce 3+ ions incorporated into PEO coatings, it can be concluded that Ce is present in all coatings (with Ce concentration increasing with PEO time) but quantification was not possible because of its low content. 19 Furthermore, from Figure 4 it can be observed that PL intensity of the broad 440 nm emission peak increases with PEO processing time, thus suggesting that the number of oxygen vacancy related defects increases with PEO processing time. This is also in line with the observed phase transformation from andalusite to sillimanite (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 91%